Comparative Study of Chamomile Tea and Commercial Artificial Tears in Post-Refractive Surgery in Dry Eye - Hafsa, Hafsa; Farhat, Iqra; Akhtar, Faiza; Shahzad, Iqra; Shaukat, Tahir; Dass, Narain (Journal of Neonatal Surgery, 2025)
Background: Dry eye, a common complication after refractive surgery, can be treated with artificial tears, but these provide temporary relief and may have limitations. Chamomile tea, known for its anti-inflammatory and soothing properties, could serve as a natural alternative therapy. Objective: To compare the effects of chamomile tea and commercial artificial tears in post-refractive surgery in dry eye. Methods: This prospective, comparative interventional study involved 30 individuals who developed dry eye symptoms after undergoing refractive surgery. The study involved participants divided into two groups: one using chamomile tea as a natural remedy and the other using conventional treatment. Participants aged 18-35, with uncomplicated refractive surgery within the last six months, and showing signs of dry eye were included. The study used the Schirmer test and Tear Break-Up Time (TBUT) tests to assess treatment adherence. An ANOVA test was used to compare mean scores within and between groups, with a significance level set at p < 0.05. Results: Participants in a study showed progressive improvement in TBUT and Schirmer scores from baseline to week 4. The Chamomile group showed higher mean TBUT (10.65 vs. 10.16) and Schirmer scores (10.62 vs. 10.06) compared to the Artificial Tears group, suggesting a potentially greater improvement in ocular surface health. The average Schirmer score was 7.43 mm (SD = 1.47), and the average TBUT was 7.56 seconds (SD = 1.51). However, no statistically significant differences were found between the two groups, indicating comparable efficacy. Conclusion: Artificial Tears and Chamomile showed progressive improvement in TBUT and Schirmer scores over four weeks, with Chamomile showing slightly higher mean scores, indicating comparable efficacy but showing no statistically significant differences.